The early childhood scaffolding scale: Conceptual framework, operationalization and functionality - Sofia Frankenberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
This study reports on work undertaken to develop a framework and rating scale for the assessment of process quality in terms of scaffolding in preschool settings. The aim was to develop the Early Childhood Scaffolding Scale (ECSS) for the assessment of interaction quality in different types of early childhood teaching practices. The ECSS was developed based on the analysis of video-recorded data from 26 preschools randomly assigned to three different pedagogical practices; 1) Social and Emotional Material Learning, 2) Digital Individual Learning and 3) Practice as usual. The scale was developed in a series of iterative steps and an abductive approach to theory and video-recorded data involving preschool practice, resulting in the specification of the framework components and the formulation of items and rating guidelines. The functionality of the scale was assessed by four raters who assessed a selection of the data. Interrater reliability (Cohen's kappa) analyses indicated multiple challenges to the construction of a reliable scale. To inform the further improvement of the framework and scale, a cognitive interview methodology was used, including think aloud and verbal probes. The findings inform the further development of the scale and factors that need to be considered in order to reach satisfactory psychometric robustness and interrater reliability, including 1) intentions of different pedagogical methods, 2) the importance of a clear conceptual framework, 3) units of analysis and the selection of ecologically valid video-recorded sequences, 4) the interpretation of items, and 5) definitions of scale values. The discussion focuses on the challenges of assessing high quality scaffolding in situated preschool settings using observational ratings and video methodology, training of raters, and the characteristics of the Swedish national preschool curriculum. Directions for future research are also suggested.
Keywords: I20; I29; 330; scaffolding; preschool; process quality; teaching; observational rating scales; video; inquiry-based pedagogy; direct instruction